Preaching Phrenitis: Augustine's Medicalization of Religious Difference - Wright, Jessica (Journal of early Christian studies, 2020)
Like many late antique preachers and theologians, Augustine of Hippo understood deviant religious practices and beliefs in terms of mental illness. Whereas this metaphor was typically framed in generic terms (for example, “madness” or “insanity”), Augustine developed a consistent and specific diagnosis that made use of the symptoms of the mental illness phrenitis (acute delirium with acute fever) to undermine the self-knowledge and authority of those who thought their spiritual health did not depend upon the healing intervention of Christ or his substitute, the Christian preacher. This article argues that Augustine used the mental illness phrenitis as a model for sickness of the soul in order to reinforce his own authority as a physician of the soul and to justify coercive therapeutic interventions in the lives of his opponents. Phrenitis represented for Augustine a sickness characterized by distorted self-perception, the rejection of medical care, preternatural physical strength, and a tendency to violence. These symptoms, which were rooted in the medical concept of the disease, established a framework for his medicalization of religious difference, both at the local level (congregants, religious opponents) and on a broader theological plane. This medicalization motivated strategies of therapeutic coercion, and enabled Augustine to define his ecclesial community along therapeutic lines.